Spectrophotometic Determination of some Sulphonamides in Aqueous Solution Via Azo- Dye Formation Reaction - N. Othman (College of Education for Pure Sciences, 2005)
A spectrophotometric method for the determination of trace amounts of some sulphonmides (six compounds) in aqueous solutions is described. The method in based on dizotisation and coupling with pyrogallol to form a yellow coloured, stable and water- soluble azo-dye which shows maximum absorption at 420 nm. Beer's law is obeyed over the concentrations range of 0.4-14 ppm. The relative error is -2.47 to + 3.41 % and the relative standard deviation is ±0.51 to ±2.9% depending on the concentration level. The proposed method has been successfully applied to the determination of sulphacetamide sodium in eye drop drug.